P190 Drug Induced Liver Injury In The Treatment Of Tuberculosis In A Busy Uk Centre. (10th November 2014) - Chitty, S; Ghani, R; Roe, JK; Davidson, H; Routledge, M; Edwards, T; Hateley, C; Collin, S; Ritchie, A; Dzvova, J; Buckley, J; Davidson, RN; et al.
Abstract : Introduction: We describe the incidence and management of drug induced liver injury (DILI) in active TB at the largest UK centre, using a nurse-led local protocol derived from 1998 BTS guidelines. Methods: All active TB cases were identified from April 2010 to May 2014. Patients were identified with DILI by following criteria: Type 1 DILI(ALT >3x upper limit normal (ULN-55iu/l), Type 2 DILI (ALP >2x ULN(150 iu/l) and Bilirubin >21 iu/l) or Type 3 DILI (Bilirubin >40 iu/l). Patient demographics, TB treatment (ATT), timing, management and outcomes of DILI were described. Baseline characteristics and ATT doses were matched with controls. Results: 105 individuals with DILI were identified out of 1529 patients with active TB (6.9%). 81% were on standard first line therapy (Rifampicin (R), Isoniazid (H), Pyrazinamide (Z) and Ethambutol (E)). 7.8% were on Moxifloxacin (M) instead of E and 1.9% were on RHME. Type 1 DILI was most frequent (81%) with median peak ALT 296 iu/l (IQR 227–505). Median time from treatment start to onset of DILI was 12.5 days (7–30). Symptoms at presentation included nausea/vomiting (54%), abdominal pain (18%) and jaundice (12.4%). 45.7% patients had all medication stopped, 7.6% continued ethambutol with amikacin (A), 26.7% continued all medication, 6.7% stopped Z only, 3.8% substituted Z for a quinolone. Median time from stopping to reintroduction was 10 days (6–17). Of 66 reintroduction patients, regimens included H >R >E(45%), H>R>E>M (31%) and R>E>M (15%). Median time from reintroduction to full treatment restart was 14 days (12–18). 81% of patients were uneventfully reintroduced, 5% suffered a 2nd DILI. 32% patients required hospital admission and 4(3.8%) died. DILI cases were matched to 200 controls. Cases more likely (P < 0.05) to; be HIV positive, have quinolones in initial regimen and lower body weight. Quinolone use gave an adjusted hazard ratio 5.41 (2.96, 9.91). Conclusion: DILI remains the most important toxicity of ATT and usually occurs during the first month. The BTS guideline provides a useful template for the diagnosis and management of DILI which may be largely nurse led and ambulatory. Most patients are successfully reintroduced without pyrazinamide. HIV status, body weight and quinolone use are risk factors.